Transnational Social Movements and Sovereignties in Transition: Charting New Interfaces of Power at the U.S.-Mexico Border - Cunningham, Hilary (Anthropologica, 2022)
This paper explores how nation-states, rather than simply withering away as many theorists of globalization claim, remain complex and important players in the production of transnational political activism. Using ethnographic research with a group of U.S. political activists at the U.S.-Mexico border, the author argues that anthropologists are uniquely poised to shift discussions about global social movements onto ethnographic terrain. Developing the notion of modalities of sovereignty, the author suggests that transnational politics be examined as culturally and historically constituted interfaces between social movements actors and states.